Effect of casting and curing temperature on the interfacial bond strength of epoxy bonded concretes. (8th November 2021) - Daneshvar, Dana; Deix, Karl; Robisson, Agathe
Highlights: Six different casting and curing temperature values from 5 to 55 °C were considered. Concrete-concrete bond strength was experimentally assessed using pull-off, wedge splitting and bi-surface shear tests. Increasing the temperature from 5 to 55 °C highly impacts the performance of epoxy bonded concretes. Characterization of individual materials reveal the three main factors contributing to the decreased interfacial bond strength with increasing casting and curing temperature. Abstract: The effect of casting and curing temperature on concrete-epoxy-concrete interfacial bond strength was evaluated. To cover a wide range of climatic conditions, six different temperature values from 5 to 55 °C were considered. The interfacial bond strength of the composites was experimentally assessed using pull-off, wedge splitting and bi-surface shear tests. The individual materials, epoxy and cement paste, were also characterized by means of viscosity, shore D hardness and setting time measurements. Results show that the casting and curing temperature dramatically impacts the mechanical properties of the epoxy bonded concretes. Indeed, increasing temperature from 5 to 55 °C leads to a decrease in bond strength up to 65%. The significant drop in setting time of epoxy compared to cement at high temperature, the inferior epoxy mechanical properties, as well as the reduction in epoxy thickness due to material loss in pores and microcracks can explain this decrease.